1979
DOI: 10.1071/ea9790673
|View full text |Cite
|
Sign up to set email alerts
|

Effects of active immunization against androstenedione or oestrone on oestrus, ovulation and lambing in Merino ewes

Abstract: Merino ewes were immunized against bovine serum albumin (BSA), or oestrone or androstenedione, conjugated to BSA. Immunization against oestrone and androstenedione elevated the mean number of ovulations per ewe ovulating (ovulation rate) from 1.2 to 1.5 and 2.3, respectively. The higher ovulation rate was not reflected in more lambs born per ewe lambing (1.12-1 .I 6 for all groups). The frequency of ovulation and oestrus was depressed in ewes immune to oestrone, and there was a high frequency of abnormalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Also it has shown that the improvement in ovulation rates after long-term immunisation compares favourably with those reported for the other breeds of sheep immunised for a shorter time interval (Scaramuzzi et al 1977;Martin et al 1978;Smith et al 1981). The primary and secondary immunisation regime produced a wide range of antibody titres at the time of mating.…”
Section: Discussionsupporting
confidence: 56%
“…Also it has shown that the improvement in ovulation rates after long-term immunisation compares favourably with those reported for the other breeds of sheep immunised for a shorter time interval (Scaramuzzi et al 1977;Martin et al 1978;Smith et al 1981). The primary and secondary immunisation regime produced a wide range of antibody titres at the time of mating.…”
Section: Discussionsupporting
confidence: 56%
“…Ovulation rate responds in a curvilinear manner to increasing titre levels, with ovulation being inhibited at high antibody titres (Martin et al 1979;Smith et al 1983;Scaramuzzi and Radford 1983;Webb et al 1984). In PMSG-treated oestradiol-immune ewes, Boland et al (1985) observed similar increases in ovulation rate and total ovarian response to superovulatory (1500 i.u.…”
Section: Discussionsupporting
confidence: 50%
“…Higher ovulation rates have been observed in ewes immunized against oestradiol, oestrone and androstenedione (Van Look et al 1978;Martin et al 1979;Scaramuzzi et al 1980) and it was thought that the increased ovulation rates were caused by the increased secretion of gonadotrophins observed in immunized animals (Martensz et al 1976Scaramuzzi et al 1980). Similarly, the increased release of LH after immunization against progesterone may play a role in regulating ovulation rate in these animals.…”
Section: Methodsmentioning
confidence: 97%